2007
DOI: 10.1038/sj.eye.6702831
|View full text |Cite
|
Sign up to set email alerts
|

Tonometer disinfection practice in the United Kingdom: A national survey

Abstract: Purpose: To assess current tonometer disinfection practice in the UK, and compare with published recommendations. Methods: Every ophthalmology unit with training recognition in the UK was contacted (n ¼ 155). A senior nurse at each institution completed a telephone questionnaire regarding local tonometer disinfection practice. Results: The response rate was 100%. Thirty-five units (23%) reported exclusive use of disposable tonometer heads and were excluded from further analysis. One hundred and twenty units (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Potential reservoirs of HAIs are different surfaces including stethoscopes [13,14], bed rails [15], faucet handles [16], and ophthalmic equipments, such as slit lamps [17], operating microscopes [18], tonometer tips [19][20][21][22], and felt-tipped marker pens [23]. In the digitial medicine also mobile phones [24] and computer keyboards [16] become more relevant vehicles for the transmission of pathogenic microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Potential reservoirs of HAIs are different surfaces including stethoscopes [13,14], bed rails [15], faucet handles [16], and ophthalmic equipments, such as slit lamps [17], operating microscopes [18], tonometer tips [19][20][21][22], and felt-tipped marker pens [23]. In the digitial medicine also mobile phones [24] and computer keyboards [16] become more relevant vehicles for the transmission of pathogenic microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…One UK study found that often only one Goldmann prism was provided per practitioner, thereby reducing the likelihood of adequate soak time between patients. 8 In a busy clinic setting, the supply must be greatly increased to avoid delay in patient care, with 200 Goldmann prisms required for routine use by practitioners. The VABHS clinic has seen a rate of damage and loss to the tips at 50% with SPD cleaning, creating a need for an additional 100 replacement tips.…”
Section: Summary Of Datamentioning
confidence: 99%
“…3,5,6 Adenovirus can survive for 7-14 days at room temperature on a dry surface and is resistant to 70% isopropyl alcohol, 7 which is often used in busy clinic settings. 8 Improper sterilization techniques also increase the risk of corneal injury and burn secondary to residual cleansing solution on reusable Goldmann prisms. 9 Therefore, in 2009, the Veterans Affairs Boston Healthcare System (VABHS) introduced single-use Tonosafe disposable tonometer prisms (Clement Clarke, Columbus, OH, USA) as an alternative to Goldmann tonometer prisms for measuring intraocular pressure (IOP) across all general and specialty eye clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Im Routineeinsatz werden diese vor allem aus Kostengründen meist nur selektiv bei Risikopatienten eingesetzt. In der klinischen Praxis werden überwiegend mehrfach verwendbare Tonometerköpfchen eingesetzt und auf Hypochlorit-Basis oder mit Wasserstoffperoxid desinfiziert[5,20]. Bei der Wahl der Desinfektionsflüssigkeit lassen die Empfehlungen von Fachgesellschaften 1:10 verdünnte Natriumhypochlorit-Lösung (i. e. 500 ppm), alternativ 3 %ige Wasserstoffperoxid-Lösung, 70 %iges Ethanol oder 70%igesIsopropanol zu [1].…”
unclassified